International course of physical education (Fiep Bulletin - online, 2015)
Organised by the Belgian Federation of Physical Education under the patronage of the FIEP this international Course in the French Language, knew a very great success. Thirteen Countries were represented: Germany (f.r.), Belgium, Canada, Danmark, Spain, France, Greece, Holland, Italy, Poland , Portugal, Sweden, South – Vietnam, totalizing 230 participants.